The Clock Genes Are Involved in The Deterioration of Atopic Dermatitis after Day-and-Night Reversed Physical Stress in NC/Nga Mice - Hiramoto, Keiichi (Open Biochem J, 2018)
BACKGROUND: In modern society, irregular lifestyles are a problem. It is well known that Atopic Dermatitis (AD) occurs during physical stress in people with an irregular lifestyle. We evaluated the influence that day-and-night reversal physical stress has on AD. METHODS: Six-week-old specific-pathogen-free and conventional NC/Nga male mice were used. For the day-and-night reversal procedure, the mice ran on a treadmill at a slow speed of 10 m/min for 12 h (between 8:00 and 20:00). Then, between 20:00 and 8:00, we put the mice in a dark place. This treatment was repeated every day for two weeks. The behavioral circadian rhythm of the mice was evaluated with the open field test. Then, the mice were sacrificed and histological examinations of the tissues, the expression of peptide hormones, corticosterone, Immunoglobulin E, histamine, and cytokines was performed using an enzyme-linked immunosorbent assay. RESULTS: In the treadmill-treated conventional NC/Nga mice, AD symptoms were deteriorated compared with the non-treated conventional NC/Nga mice. The levels of Period (Per) 2, Clock, and brain and muscle arnt-like protein 1 (Bmal1) in the skin were increased constantly in the treadmill-treated conventional mice. Furthermore, the expression of Retinoic Acid-related Orphan Receptor (ROR)α, which activates Bmal1, was increased in the treadmill-treated conventional mice compared with the non-treated conventional mice. In addition, when non-treated conventional mice were administrated by the agonist of RORα, AD symptoms were deteriorated similar to treadmill-treated conventional mice. CONCLUSION: In the day-and-night reversal mice, the clock genes were increased constantly, indicating that this is a factor that deteriorated AD.